Smart systems commissioning for energy efficient buildings. (March 2016) - Noye, Sarah; North, Robin; Fisk, David
The gap between as-designed and as-operating energy consumption of new buildings has been widely recognized. Commissioning for optimal energy performance should be a key process to remedy this but in practice, due to shortages of time and budget, commissioning is often limited to ensuring 'practical completion' and minimum year-round energy consumption may not be achieved. Commissioning implementation suffers, historically, from poor availability of real time data. Portable wireless sensor networks offer substantial opportunities to support energy-efficient seasonal commissioning by giving temporary access to additional, continuously and simultaneously monitored data points. This paper describes a strategy to implement 'smart commissioning' through portable wireless sensor networks for air conditioning systems. Key requirements for delivering seasonal commissioning strategies of multi-modal systems are discussed. Practical application : The importance of post-occupancy commissioning in delivering good energy and environmental performance of new buildings is now widely recognised through practices such as soft landings. However, troubleshooting can be difficult when the building is occupied and budget to do this limited. The building management system may identify that there is a problem but is very unlikely to be collecting the necessary forensic data to solve it. Portable wireless sensor networks specifically designed for analysing building services can overcome this problem in a convenient and economical way and can help development of new industry tools to close the performance gaps and demonstrate in-use building performance.